Calibration of a catadioptric omnidirectional vision system with conic mirror - Marcato Junior, J. (2016)
Omnidirectional vision systems that enable 360° imaging have been widely used in several research areas, including close-range photogrammetry, which allows the accurate 3D measurement of objects. To achieve accurate results in Photogrammetric applications, it is necessary to model and calibrate these systems. The major contribution of this paper relates to the rigorous geometric modeling and calibration of a catadioptric, omnidirectional vision system that is composed of a wide-angle lens camera and a conic mirror. The indirect orientation of the omnidirectional images can also be estimated using this rigorous mathematical model. When calibrating the system, which is composed of a wide-angle camera and a conic mirror, misalignment of the conical mirror axis with respect to the camera's optical axis is a critical problem that must be considered in mathematical models. The interior calibration technique developed in this paper encompasses the following steps: wide-angle camera calibration; conic mirror modeling; and estimation of the transformation parameters between the camera and conic mirror reference systems. The main advantage of the developed technique is that it does not require accurate physical alignment between the camera and conic mirror axis. The exterior orientation is based on the properties of the conic mirror reflection. Experiments were conducted with images collected from a calibration field, and the results verified that the catadioptric omnidirectional system allows for the generation of ground coordinates with high geometric quality, provided that rigorous photogrammetric processes are applied.